2020
DOI: 10.1101/2020.08.04.20168013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of COVID-19 and comorbidity co-infection Model with Optimal Control

Abstract: The new coronavirus disease 2019 (COVID-19) infection is a double challenge for people infected with comorbidities such as cardiovascular and cerebrovascular diseases and diabetes. Comorbidities have been reported to be risk factors for the complications of COVID-19. In this work, we develop and analyze a mathematical model for the dynamics of COVID-19 infection in order to assess the impacts of prior comorbidity on COVID-19 complications and COVID-19 re-infection. The model is simulated using data relevant to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…Mathematical modelling has been used extensively in studying the behaviour of infectious diseases, including their co-infections [1,7,13,18,23,28,41,43,44]. Particularly, Several mathematical models have been developed to understand the transmission dyanamics of Chlamydia trachomatis infections.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modelling has been used extensively in studying the behaviour of infectious diseases, including their co-infections [1,7,13,18,23,28,41,43,44]. Particularly, Several mathematical models have been developed to understand the transmission dyanamics of Chlamydia trachomatis infections.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, mathematical models have been developed, incorporating optimal control strategies for the dynamics of infectious diseases, including their co-infections. [25][26][27][28][29][30][31][32][33][34] More recently, Egeonu et al 27 studied a co-infection model for drug-resistant malaria and cholera with optimal control. Numerical simulations of their model revealed that malaria drug resistance can greatly influence the co-infection cases averted, even in the presence of treatment controls for co-infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, mathematical models have been developed to consider the optimal control strategies for the dynamics of infectious diseases including their co-infections [1, 9, 11, 20, 26, 27, 31, 32, 34]. Agusto and Adekunle [1] studied the optimal control and cost-effectiveness analysis of the co-infection of drug-resistant tuberculosis and HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%